Museum ship news from the Maritime Museum of Finland - Aartomaa, Johanna; Puustinen, Juha (Tekniikan Waiheita, 2021)
This short article delves into the upkeep and docking of the largest heritage ships in the collections of the Maritime Museum of Finland in Kotka, Southeastern Finland. Steam driven icebreaker Tarmo was docked in 2016–2017, and lightship Kemi taken to dry dock late in 2020. Both ships are nationally significant museum vessels that were laid aside for this heritage purpose immediately after their operational life had ended. The article highlights the various research and collections activities needed in the long term maintenance and docking of such ships, and some of the surprises the museum ran into. Katsaus käsittelee Suomen merimuseon suurimpien museoalusten ylläpitoa. Höyryjäänmurtaja Tarmo telakoitiin viimeksi vuosina 2016–2017, ja majakkalaiva Kemin tekointi alkoi talvella 2020–2021. Molemmat alukset ovat kansallisesti merkittäviä museolaivoja, jotka on päätetty museoida heti käyttövuosiensa jälkeen. Katsaus avaa suurten museolaivojen telakointiin liittyvää tutkimusta, työtehtäviä ja yllätyksiä.